2016
DOI: 10.1007/s00382-016-3101-z
|View full text |Cite
|
Sign up to set email alerts
|

Moisture increase in response to high-altitude warming evidenced by tree-rings on the southeastern Tibetan Plateau

Abstract: Rapid warming has been observed in the high-altitude areas around the globe, but the implications on moisture change are not fully understood. Here we use tree-rings to reveal common moisture change on the southeastern Tibetan Plateau (TP) during the past five centuries, and show that regional moisture change in late spring to early summer (April-June) is closely related to large-scale temperature anomaly over the TP, with increased moisture coincident with periods of high temperature. The most recent pluvial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 66 publications
9
35
1
Order By: Relevance
“…The rising temperature could further amplify drought stress by increasing evapotranspiration rates or by raising vapor pressure deficit [24]. This is supported by previous studies from the Himalayas and surrounding areas [5,6,9,10,15,34,43]. In contrast, a significant positive correlation between tree growth and temperature was observed in the central Himalayas [4,7,13].…”
Section: Climate-and Drought-growth Associations: the Pivotal Role Ofsupporting
confidence: 54%
See 1 more Smart Citation
“…The rising temperature could further amplify drought stress by increasing evapotranspiration rates or by raising vapor pressure deficit [24]. This is supported by previous studies from the Himalayas and surrounding areas [5,6,9,10,15,34,43]. In contrast, a significant positive correlation between tree growth and temperature was observed in the central Himalayas [4,7,13].…”
Section: Climate-and Drought-growth Associations: the Pivotal Role Ofsupporting
confidence: 54%
“…Previous studies in the central Himalayas have shown that pre-monsoon precipitation is the major growth-limiting factor for Himalayan birch (Betula utilis) [5,6], Himalayan fir (Abies spectabilis) [8], alpine dwarf shrubs (Cassiope fastigiata) [31], Himalayan spruce (Picea smithiana), Himalayan blue pine (Pinus wallichiana) [9,10], and Chir pine (Pinus roxburghii) [22]. Similar growth responses in different conifer trees species were also reported from surrounding areas such as in the western Himalayas [11,12,32,33], subtropical broadleaf tree Toon (Toona ciliata) in the eastern Himalayas [17], and in the southeastern Tibetan Plateau [34,35]. However, our study shows that precipitation from November of the previous year to April of the growth year limits the radial growth of Chir pine, suggesting a stronger drought stress for tree growth in the subtropical forest belt in the central Himalayas.…”
Section: Climate-and Drought-growth Associations: the Pivotal Role Ofmentioning
confidence: 69%
“…Past, 14, 1213-1228, 2018 Scots pine usually has a typical climate (drought) response pattern with positive tree growth response to increasing precipitation and a negative response to increasing temperature (Bao et al, 2015;Davi et al, 2006;Liu et al, 2009). This typical drought response pattern is usually found in other drought or wetness tree-ring reconstructions (Li et al, 2016;Liu et al, 2017). In this study, the correlation between treering index and monthly precipitation and temperature revealed that the radial growth of Scots pine was mainly limited by water, which is consistent with the physiological characteristics of tree species living in semi-arid regions.…”
Section: Climate-growth Relationshipsupporting
confidence: 67%
“…Similar results were also found by Dai (2013), which presented a different dry-wet pattern under global warming using observations and models. In the Tibetan Plateau, Li et al (2016) found moisture increases related to rapid warming (warmwet). Although the reason for this divergence should be further studied, it might be related to the different response to the phase shift (negative to positive) of the PDO in 1976and 1977(Ma, 2007Wang et al, 2014).…”
Section: Comparison With Regional Recordsmentioning
confidence: 99%
See 1 more Smart Citation